Disease Prevalence and Its Consequences on Blood Metabolites, Physical Activities, Milk Yield, and Fertility - J. S. Stevenson; S. Banuelos (Kansas Agricultural Experiment Station Research Reports, 2019)
Health status of 160 lactating cows was monitored by assessing blood metabolites on days 0, 3, 7, and 14 after calving, in addition measures of physical activity during 20 days surrounding parturition. Cows with clinical disease (any with diagnosis of ketosis, metritis, mastitis, respiratory disease, or milk fever during the first 60 days in milk) were compared with outcomes in healthy cows. Expected differences were observed between health status groups for serum concentrations of free fatty acids, beta-hydroxybutyrate, haptoglobin, and calcium, but not for plasma glucose. Daily postpartum rumination and eating times were decreased in diseased cows and they spent more time resting or being inactive. Body condition scores decreased more in diseased cows, whereas body weight and milk yield were unaffected by health status. Despite early and proportionally more ovulations during the prebreeding period in healthy cows, pregnancy rate at first service and days to conception were not affected by health status, likely because of good health care of all cows having both clinical and subclinical disease.
Keywords: ovulation; dairy cow; disease